2010
DOI: 10.1124/jpet.109.164277
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Stimulation of d-Aspartate Uptake into Human SH-SY5Y Neuroblastoma Cells Is Attenuated by Hypoosmolarity

Abstract: In addition to its function as an excitatory neurotransmitter, glutamate plays a major role as an osmolyte within the central nervous system (CNS). Accordingly, mechanisms that regulate glutamate release and uptake are of physiological importance not only during conditions in which cell volume remains constant but also when cells are subjected to hypoosmotic stress. In the present study, the ability of muscarinic cholinergic receptors (mAChRs) to regulate the uptake of glutamate (monitored as D-aspartate) into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In addition, a reduction in the glial and neuronal glutamate uptake may contribute to the hypoosmotic increase in extracellular glutamate. A reduction in the glutamate uptake under hypoosmotic conditions was recently described in neuroblastoma cells (Foster et al 2010).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, a reduction in the glial and neuronal glutamate uptake may contribute to the hypoosmotic increase in extracellular glutamate. A reduction in the glutamate uptake under hypoosmotic conditions was recently described in neuroblastoma cells (Foster et al 2010).…”
Section: Discussionmentioning
confidence: 79%
“…A reduction in the glutamate uptake under hypoosmotic conditions was recently described in neuroblastoma cells (Foster et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Foster and coworkers found that treatment with oxotremorine-M, a non-selective muscarinic acetylcholine receptor agonist that can activate PKC, increased the plasma membrane localization of EAAT3, an effect that was partially sensitive to PKC and PI3K inhibitors (Foster et al, 2010). PI3K-mediated EAAT3 increase in surface expression is stimulated by platelet-derived growth factor (PDGF) (Sims et al, 2000).…”
Section: Regulation Of Eaat3mentioning
confidence: 99%
“…As observed for the taurine transporter, the osmosensitive attenuation of glutamate uptake reflects a reduction in the V max for transport without a change in K m and was accompanied by an altered trafficking pattern of the transporter (Fig. 3; Foster et al 2010). Endothelin‐1‐stimulated increases in glutamate uptake into C 6 glioma cells (mediated by EAAT3) were similarly attenuated by hyposmolarity indicating that receptor‐mediated regulation of glutamate transport may be a general, rather than cell‐specific, phenomenon.…”
Section: Is Osmolyte Influx An Additional Mechanism Whereby Gpcrs Canmentioning
confidence: 53%
“…To determine whether similar or distinct mechanisms exist for glutamate and taurine homeostasis, glutamate uptake into SH‐SY5Y cells (monitored as d ‐[ 3 H]aspartate influx) was measured as a function of osmolarity and receptor activation. Glutamate uptake was substantially increased under isotonic conditions by activation of mAChRs and to a lesser extent by endothelin or LPA receptors (Foster et al 2010). The mAChR‐mediated enhancement of glutamate uptake, which required the presence of Ca 2+ and activation of PKC and PI3K, was mediated by a cellular redistribution to the plasma membrane of the excitatory amino acid transporter 3 (EAAT3), a neuron‐specific transporter.…”
Section: Is Osmolyte Influx An Additional Mechanism Whereby Gpcrs Canmentioning
confidence: 99%